JEP 2019
DOI: 10.7176/jep/10-17-07
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Classroom Environment on Students` Performance in English Language

Abstract: The objectives of the study are to examine impact of classroom environment on the academic performance of students in English language as well as their performance difference by gender. Survey and Correlation research designs were employed. The population of the study involved 183 teachers and 2003 SS III students in the selected schools. 401 students representing 20% and 183 teachers were randomly selected. Self-developed questionnaire and profoma were used for collection of data for this study. The data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…The implication is that as Economics teachers' management of the classroom A model of effective teaching of Economics in higher education: the integral role of classroom learning environment, instructional practices, and teacher characteristics learning environment improves by 1 standard deviation unit, their engaging and interactive lessons improve by .117. This means that as Economics teachers create and manage a classroom learning environment that fosters personal interaction conducive to learning, providing opportunities for students' minds and imaginations to be engaged (Walli, Abulfathi and Mustapha, 2019), students' learning experiences improves. Phillips, McNaught and Kennedy (2010) similarly found that teachers' quality instructional practices are strongly influenced by the learning environment in the classroom.…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The implication is that as Economics teachers' management of the classroom A model of effective teaching of Economics in higher education: the integral role of classroom learning environment, instructional practices, and teacher characteristics learning environment improves by 1 standard deviation unit, their engaging and interactive lessons improve by .117. This means that as Economics teachers create and manage a classroom learning environment that fosters personal interaction conducive to learning, providing opportunities for students' minds and imaginations to be engaged (Walli, Abulfathi and Mustapha, 2019), students' learning experiences improves. Phillips, McNaught and Kennedy (2010) similarly found that teachers' quality instructional practices are strongly influenced by the learning environment in the classroom.…”
Section: Hypothesismentioning
confidence: 99%
“…Historically, studies concerning the teaching of Economics in higher education institutions have concentrated on a limited number of classroom instructional activities (for example, methods of teaching and use of teaching learning materials). However, substantial empirical evidence (Dees, 2007;Danielson, 2013;Blazar, 2017;Walli, Abulfathi and Mustapha, 2019) The role of Economics teachers in contributing to student learning in Economics has been contentious. The bone of contention here has to do with the conceptualisation of students' learning outcomes.…”
Section: Introductionmentioning
confidence: 99%